Interpreting the edge angle efficiency of middle palaeolithic lithic assemblage with Artifact-3D – A case study Barwaniya W1, North Karanpura Valley, Eastern India - Shubham Rajak; Pronil Das (Quaternary Environments and Humans)
The lithic technology is directly linked with knapping skills, cognition, and economic production of a particular culture. The central objective of lithic production was to obtain desirable edge angles and sharpness for cutting/ butchering work in an efficient manner to achieve the highest utility/ efficiency and low production ratio. The angle of an edge, whether unaltered or retouched and as part of the overall tool design, is undoubtedly a parameter that influences the behavioural dimension of a lithic artefact. Thus, lithics artefacts' work efficiency or knapping efficiency depends on their working (cutting) edge angle, length of the parallel edge, centre of gravity, length of lithic, and lesser rate of edge angle damage. The present research has analysed the working edge angle of the Middle Palaeolithic Levallois assemblage from the newly discovered site of Barwaniya W1 from the North Karanpura Valley (North of Upper Damodar Basin), Jharkhand, India with the help of semi-automated 3D edge angle analysis technique. the current study scrutinises the entirety of an artefact's edge angle through automated positioning based on surface tension and a higher number of reference measurement points on the 3D scan surface of the artefact. This research has digitally measured the Middle Palaeolithic quartzite flake-based assemblage from Barwaniya W1 and their working edge angle, parallel edge (thick blunt side used for hafting), and centre of gravity with Artefact-3D software which has provided us with precise measurement without human errors and ambiguity. Further, this research has replicated the quartzite lithic assemblage of Barwaniya W1 with the Levallois reduction technique to interpret the edge angle efficiency.